2012
DOI: 10.1007/s13197-012-0882-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects on colour characteristics of buffalo meat during blooming, retail display and using vitamin C during refrigerated storage

Abstract: Experiments were conducted to determine the effect of blooming, retail display and vitamin C on colour changes/improvement of buffalo meat. To evaluate the effect of blooming, top round cuts of buffalo were allowed to bloom for 60 min. As colour bloomed, a* value increased from 6.47 to 10.01 at 45 min; no further changes occurred. In another study, top round cuts were kept at ambient temperature (36±2°C) and evaluated for instrumental colour during display. The instrumental redness value (a*) and chroma signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…For striploin muscle, there was no noticeable correlation between the brightness and the consumers' evaluations of the beef. Even though it has been claimed that the color of meat is most dependent on a* parameter (Dlivera et al, 2013;Sen et al, 2014), in our experiment a strong negative correlation was observed between the a* and b* values and the consumer color evaluations (r > 0.7 at significance level of 0.05). This suggests that yellowness is as important as redness in the consumer assessment.…”
Section: Relationship Between the Instrumental Parameters And Consumecontrasting
confidence: 70%
See 1 more Smart Citation
“…For striploin muscle, there was no noticeable correlation between the brightness and the consumers' evaluations of the beef. Even though it has been claimed that the color of meat is most dependent on a* parameter (Dlivera et al, 2013;Sen et al, 2014), in our experiment a strong negative correlation was observed between the a* and b* values and the consumer color evaluations (r > 0.7 at significance level of 0.05). This suggests that yellowness is as important as redness in the consumer assessment.…”
Section: Relationship Between the Instrumental Parameters And Consumecontrasting
confidence: 70%
“…Exposing the meat to carbon monoxide before vacuum packaging significantly prevented the discoloration of the meat surface during storage. Sen et al (2014) reported a higher degree of discoloration (>60%) for vacuum-packed beef after 9 days of refrigerated storage.…”
Section: Consumer Assessmentmentioning
confidence: 95%
“…In addition to differences in the category of the slaughtered animals and the production systems, other factors, including mainly pre-slaughter handling of the animals, postslaughter treatment of the carcass, and length of the storage period, can affect the meat colour [134]. Sen et al [135] observed that the bloom time had a significant effect on all the colour parameters, with values continuously changing for 60 min, leading to a significant decrease in L* and increase in a* and b*. The same authors showed that the retail display time also had a significant effect on instrumental colour characteristics of buffalo meat, with the a* value significantly increasing after 12 h of display.…”
Section: Trait Rangementioning
confidence: 99%
“…Physiological leanness resulting from lack of feed and water should be differentiated from pathological leanness due to disease. The grading criteria ensure that only quality beef carcasses are sold as meat to consumers [31,32]. According to Codex Alimentarius, (1993) the responsibility for the production of safe and wholesome meat should be shared by industry and the controlling authority.…”
Section: Beef Carcass Classification In the European Unionmentioning
confidence: 99%